DO SUBMERGED BARS PROTECT THE BEACH? - KHATIZAH (NIM: 20107069), ELIS
We consider waves pass over a seabed covered with parallel bars as wave reflector. In the previous research an optimal dimension of the submerged parallel bars is obtained. The more bars installed, the more incident wave amplitude is reduced. In that study we assume the beach is ideal and can absorb all transmitted wave energy. When there is some reflection from the beach, several literature suggest that submerged bars may increase the hazards to the beach. This mechanism depends on the distance between the bars and the wall. In this paper, we study the effect of submerged bars breakwater where there is a hard-wall beach on the right. From the phase difference between several right running waves that superpose and hit the hard-wall beach, we can obtain the formula for the safest distance, and the most dangerous one. The safest distance is obtained when the right running wave superpose destructively, and the most dangerous distance is obtained when the wave superpose constructively. This argument is an approximation. Numerically, we apply the characteristic method that can give an exact solution. It turns out that numerical computations confirm the above formula. Hence, we conclude that submerged parallel bars have to be placed certain distance away from the beach in order to function as a protection.